RANCANGAN APLIKASI TAGIHAN JASA PENILAIAN ASET PADA KANTOR PENILAI PUBLIK MUTTAQIN BAMBANG PURWANTO ROZAK USWATUN - Irma Suana (JURNAL AKADEMIKA)
Valuation of assets is one of the sub- sectors of the services that can play an important role in determining the economic value of assets and the potential wealth that we have . In Indonesia , the valuation of assets have not been recognized in general . This is because the valuation of assets still in the early stages and are in growth . Assets are items or objects or an item / object that can be owned and that have economic value (economic value) , the value of commercial or exchange value that is owned or used a business entity , entities or individuals . Meanwhile , the Office of Asset Valuation Services is external to the institution of independent financial institutions in assessing the assets of a company .